Student’s Communication Accomodation From Different Region in English Department - Rahmadani, Putri (Language Horizon: Journal of Language Studies, 2024)
This study aims to explain and analyze the communication accommodation process that students go through from different regions when they first meet and converse with Surabaya native students. When out-ofregion students begin their studies at a college far from their home, they frequently confront difficulties adjusting to a new social and cultural context. This study takes a qualitative approach to data collection by conducting in-depth interviews with out-of-region students who have gone through the experience. According to this study’s findings, students from different regions suffer many communication obstacles during their first contact and interactions with Surabaya students. These problems include dialect and accent variances, disparities in nonverbal language use, and cultural values and traditions that affect interpersona to cmmunication. This study will use Giles’ theory of Communication Accommodation (CAT). According to CAT, individuals adjust their communication patterns to conform to or deviate from the speech norms of the people with whom they interact. This theory provides a comprehensive framework for analyzing communication accommodation in different areas. The findings of this study provide insights into the dynamics of cross-cultural communication in academic environments. They can be used to build support programs to help out-of-region students adapt well to their new environment. The author chose to analyzet his topic because the author is a person from a different region studying in Surabaya, and the author hasa lso gone through the communication adjustment process and initially struggled with it.